Topološka svetloba - Ogrinec, Urban (Matrika, 2020)
The article describes the behaviour of photons in topologically nontrivial materials by way of analogy with electrons in topological insulators. In the first theoretical part some key notions regarding understanding of topological light are explained e.g. Bloch states, Berry phase and Berry curvature, the latter two generalizing the concept of vector magnetic potential and flux through an arbitrary manifold, respectively. Furthermore, Chern invariant is defined together with an influence symmetries have on 2D and 3D topological phases. The second part of the article is dedicated upon applications regarding guidance and control of topological light, in particular on a microscale. In the end discussion touches upon some selected experiments in the field.
Keywords: Berry curvature; Berryjeva ukrivljenost; časovna simetrija; Diracovi stožci; Dirac's cones; fotoni; kvantna Hallova topološka faza; photons; quantum Hall topological phase; time symmetry; topologija svetlobnih polj; topology of light fields